Study on growth and yield of some aromatic rice varieties (Bangladesh Agronomy Journal, 2023)
A field experiment was conducted at Agronomy field of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka during the period from June to December 2017 with seventeen aromatic rice varieties viz., V1= Chiniatap 1, V2= Chiniatap 2, V3= Kataribhog 1, V4= Kataribhog 2, V5= BRRI dhan34, V6= BRRI dhan37, V7= BRRI dhan38, V8= BR5/Dulabhog, V9= Khoisanne, V10 = Sadasanne, V11= Zirabhog, V12= Begun bichi, V13= Shakkhorkhora, V14= Chinigura, V15= Kalijira, V16= Badshabhog, V17= Modhumala to study on growth and yield of some aromatic rice varieties. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Regarding growth and yield parameters, the highest number of total tillers hill−1 (23.33), leaf area index (5.38), flag leaf length (30.12 cm), number of effective tillers hill−1 (21.67), panicle length (32.00 cm), number of grains panicle−1 (230.3), number of filled grains panicle−1 (212.7), grain yield (3.42 t ha−1), straw yield (6.19 t ha−1) and number of biological yield (9.610 t ha−1) were found in var. BRRI dhan37 but the highest 1000- grains weight (22.80 g) and harvest index (37.48%) were found Modhumala followed by  BRRI dhan34, respectively. The lowest number of effective tillers hill−1 (13.33), panicle length (24.67 cm), grain yield (1.583 t ha−1), straw yield (4.083 t ha−1), biological yield (5.667 t ha−1) and harvest index (27.89%) were found in the var. Modhumala.Bangladesh Agron. J. 2023, 26(1): 1-8